The effect of Islamic Financial Literacy and religiosity on the interest of saving Generation Z in Islamic banks - Husnul Khotimah; Noorikha Pandayahesti Saputeri; warsiyah (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2024)
The growth of savings interest in generation z is inseparable from the influence of social media. The growth of interest in saving gen z at Islamic banks is inseparable from a good social media marketing strategy. The purpose of this study is to determine how sharia financial knowledge and religiosity influence the decision of University of Muhammadiyah Lampung students to save at Islamic banks. In this study, interest in saving as the dependent variable, and Islamic financial literacy and religiosity as the dependent variable. This research using a quantitative approach. The population in this study were Students of the Faculty of Islamic Religion at Muhammadiyah Lampung University class 2020-2023. The primary data used came from a questionnaire with a total of 100 respondents. The sampling technique used non-probability sampling technique. The analysis technique in the study used multiple regression analysis analysis and processed using spss. The results showed Fcount is greater than Ftable, namely 38.743 smaller than 2.669 and Ho is accepted. This shows that sharia financial literacy (X1) and religiosity (X2) affect the interest in saving (Y) simultaneously.